ANALISIS PENGELOLAAN ZAKAT PRODUKTIF PADA BAZNAS KABUPATEN SAROLANGUN - muhammad ivan septian; Elyanti rosmanidar; Ahsan putra hafiz (Journal of Student Research, 2024)
This research focuses on "Analysis of Productive Zakat Management at BAZNAS Sarolangun Regency". The research aims to find out how effective productive zakat management is and the suitability of its implementation with Law No. 23 of 2011 concerning zakat management. This research uses a qualitative type of descriptive research with a case study approach. This research uses two data sources, namely primary data in the form of interviews and secondary data in the form of book references and the internet/or official website related to this research. This type of research uses data collection, namely interview techniques, field observation and documentation. The results of the research show that the management of productive zakat at BAZNAS Sarolangun Regency is largely in accordance with Law Number 23 of 2011 with several things that need to be improved to make it more effective, such as a lack of supervision due to the lack of members from BAZNAS Sarolangun Regency